2011
DOI: 10.1007/s11630-011-0454-9
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in heat transfer of endothermal hydrocarbon fuel

Abstract: Numerical studies under supercritical pressure are carried out to study the heat transfer characteristics in a single-root coolant channel of the active regenerative cooling system of the scramjet engine, using actual physical properties of pentane. The relationships between wall temperature and inlet temperature, mass flow rate, wall heat flux, inlet pressure, as well as center stream temperature are obtained. The results suggest that the heat transfer deterioration occurs when the fuel temperature approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The previous studies of deterioration phenomena in heat transfer to supercritical fluids indicated that: at a certain inlet temperature, the onset of HTD depends on the combined effects of pressure, mass flux and heat flux [9,15,16,30,31]. For supercritical inorganic substances, such as water and carbon dioxide, Yamagata et al [30], Styrikovich et al [31], Kim et al [9] developed respectively a series of corrections for critical heat flux of HTD, and concluded that it was only related to the mass flux.…”
Section: Critical Condition For the Onset Of Htdmentioning
confidence: 99%
See 4 more Smart Citations
“…The previous studies of deterioration phenomena in heat transfer to supercritical fluids indicated that: at a certain inlet temperature, the onset of HTD depends on the combined effects of pressure, mass flux and heat flux [9,15,16,30,31]. For supercritical inorganic substances, such as water and carbon dioxide, Yamagata et al [30], Styrikovich et al [31], Kim et al [9] developed respectively a series of corrections for critical heat flux of HTD, and concluded that it was only related to the mass flux.…”
Section: Critical Condition For the Onset Of Htdmentioning
confidence: 99%
“…For supercritical inorganic substances, such as water and carbon dioxide, Yamagata et al [30], Styrikovich et al [31], Kim et al [9] developed respectively a series of corrections for critical heat flux of HTD, and concluded that it was only related to the mass flux. However, the related studies for organic substances, including the methane [15] and pentane [16], have also been conducted by Urbano et al [15] and Zhou et al [16], both of which further considered the effect of pressure. The details of these empirical expressions are in Table 2.…”
Section: Critical Condition For the Onset Of Htdmentioning
confidence: 99%
See 3 more Smart Citations